2019
DOI: 10.1016/j.ajo.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timolol on Aqueous Humor Outflow Facility in Healthy Human Eyes

Abstract: Purpose: Hyposecretion of aqueous humor has been postulated to adversely affect trabecular meshwork health and outflow resistance. However, the effect of medications that reduce aqueous humor production on outflow facility in living human eyes is unclear. In this study we evaluated the effect of timolol, an aqueous humor flow suppressant, on outflow facility in healthy eyes.Design: Prospective, before-and-after study. Methods:In a multicenter study, 113 healthy participants over age 40 years were included. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…After timolol treatment, the authors observed that the eye with a higher outflow facility had a larger posttreatment decrease in the outflow facility to achieve a stable IOP level. 35 Various explanations have been proposed for the mechanism by which outflow facility may modulate IOP and retain a stable pressure. Stamer et al 36 hypothesized that the outflow resistance within the conventional outflow pathway is constantly adjusted in response to the cell stretch caused by the fluctuating IOP; the mechanism might involve extracellular matrix turnover but would require hours and up to several days.…”
Section: Discussionmentioning
confidence: 99%
“…After timolol treatment, the authors observed that the eye with a higher outflow facility had a larger posttreatment decrease in the outflow facility to achieve a stable IOP level. 35 Various explanations have been proposed for the mechanism by which outflow facility may modulate IOP and retain a stable pressure. Stamer et al 36 hypothesized that the outflow resistance within the conventional outflow pathway is constantly adjusted in response to the cell stretch caused by the fluctuating IOP; the mechanism might involve extracellular matrix turnover but would require hours and up to several days.…”
Section: Discussionmentioning
confidence: 99%
“…2 Therefore, the mode of action of current medications includes a decrease of AH production or increase of AH outflow by the TM or uveoscleral pathway or both. 3,4 Through our systems genetics investigations, we identified Cacna2d1, a subunit of the L-type calcium channel, as a gene modulator of IOP. Our previous study demonstrated that CACNA2D1 is localized to the CB (area of AH production) and TM (area of conventional AH drainage) in both mouse and human eyes leading us to predict that pregabalin (PRG), a gabapentinoid drug with high affinity and high selectivity for CACNA2D1, would lower IOP by decreasing the production or increasing the drainage of aqueous humor from the eye.…”
mentioning
confidence: 80%
“…Fortunately, IOP can be medically controlled; thus, IOP reduction is the first-line therapeutic option in glaucoma . Therefore, the mode of action of current medications includes a decrease of AH production or increase of AH outflow by the TM or uveoscleral pathway or both. , …”
mentioning
confidence: 99%
“…For example, Timolol was a first-line drug for lowering IOP by blocking the beta-adrenergic receptors in the ciliary body 20 to decrease aqueous humor flow 21 . More recently, timolol has been shown to have an effect on outflow facility 22 , which also impacts IOP. The other five genes are targets in many clinical trials involving razuprotafib, ataluren, ELX-02, MT-3724, roxadustat, daprodustat, vadadustat, and perhexiline, which provide candidates for drug repurposing for possible glaucoma treatment.…”
Section: Discussionmentioning
confidence: 99%